Epithelial cell cluster size affects force distribution in response to EGF-induced collective contractility - Chiara Zambarda; Carlos Pérez González; Andreas Schoenit; Nisha Veits; Clara Schimmer; Raimund Jung; Dirk Ollech; Joel Christian; Pere Roca-Cusachs; Xavier Trepat; Elisabetta Ada Cavalcanti-Adam (European Journal of Cell Biology, 2022)
Several factors present in the extracellular environment regulate epithelial cell adhesion and dynamics. Among them, growth factors such as EGF, upon binding to their receptors at the cell surface, get internalized and directly activate the acto-myosin machinery. In this study we present the effects of EGF on the contractility of epithelial cancer cell colonies in confined geometry of different sizes. We show that the extent to which EGF triggers contractility scales with the cluster size and thus the number of cells. Moreover, the collective contractility results in a radial distribution of traction forces, which are dependent on integrin β1 peripheral adhesions and transmitted to neighboring cells through adherens junctions. Taken together, EGF-induced contractility acts on the mechanical crosstalk and linkage between the cell-cell and cell-matrix compartments, regulating collective responses.